Determining the color index of transformer insulating oil using UV-Vis spectroscopy - Sing L.Y.; Ker P.J.; Jamaludin M.Z.; Ismail A.; Abdullah F.; Mun L.H.; Shukri C.N.S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bandwidth; Color; Insulating oil; Materials testing; Power transformers; Ultraviolet visible spectroscopy; Absorbances; American society for testing and materials; Color index; Measuring tools; Optical absorbance; Spectral response; Transformer oil samples; UV-vis spectroscopy; Oil filled transformers